2012
DOI: 10.1186/1756-0500-5-89
|View full text |Cite
|
Sign up to set email alerts
|

Functional, cognitive and psychological outcomes, and recurrent vascular events in Pakistani stroke survivors: a cross sectional study

Abstract: BackgroundThere is little direct data describing the outcomes and recurrent vascular morbidity and mortality of stroke survivors from low and middle income countries like Pakistan. This study describes functional, cognitive and vascular morbidity and mortality of Pakistani stroke survivors discharged from a dedicated stroke center within a nonprofit tertiary care hospital based in a multiethnic city with a population of more than 20 million.MethodsPatients with stroke, aged > 18 years, discharged alive from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 46 publications
2
25
1
9
Order By: Relevance
“…In addition, an improvement in acute stroke care may have led to an overall reduction in the percentage of stroke hospitalizations resulting in death in the United States. While there have been reports of reduction in stroke incidence and mortality in developed countries, the opposite has been observed in low-to-middle income countries [71]. However, the overall early stroke case fatality in low-to-middle income countries is found to be 25% higher than that seen in high-income countries in the past decade.…”
Section: The Global Burden Of Cerebrovascular Accidentmentioning
confidence: 46%
See 1 more Smart Citation
“…In addition, an improvement in acute stroke care may have led to an overall reduction in the percentage of stroke hospitalizations resulting in death in the United States. While there have been reports of reduction in stroke incidence and mortality in developed countries, the opposite has been observed in low-to-middle income countries [71]. However, the overall early stroke case fatality in low-to-middle income countries is found to be 25% higher than that seen in high-income countries in the past decade.…”
Section: The Global Burden Of Cerebrovascular Accidentmentioning
confidence: 46%
“…People ≥80 years old with stroke had a longer length of stay in contrast to younger patients (24.7 ± 27.6 vs. 22.3 ± 24.2 days; p = 0.013) [70]. Furthermore, case fatality rate for the same age group can be as high as 21% [71]. Although age seems to influence activities of daily living recovery, it has not been found to have an outcome on neurological recovery [72].…”
Section: Effect Of Age On Outcomesmentioning
confidence: 99%
“…Those significant predictors are age and baseline disability [15][16][17][18]. The study of Khan et al reported that older age was one of the independent predictors of poor functional outcome with adjusted OR of 2.1 [19]. In our study, the independent factors associated with the improvement in functional score included LOS, onset to admission interval, and depression score.…”
Section: Discussionmentioning
confidence: 60%
“…The BI represents severity of disability and is categorized into 5 scales according to the scores. Those were very severely disabled (score 0-4), severely disabled (score 5-9), moderately disabled (score [10][11][12][13][14], mildly disabled (score [15][16][17][18][19], and independent (score 20) [12].…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] Besides that, among all chronic debilitating burdens associated with stroke, [5][6][7][8] depression is one of most common conditions that arise among stroke survivors [7][8][9][10][11][12][13][14][15][16] in higher levels compared to other clinical and nonclinical populations. 17,18 Previous prospective studies, mostly from high-income countries including population-and hospitalbased samples mainly based on ischemic stroke cases, suggest a wide variation in depressive symptoms (15.4%-54%) [7][8][9][10][11]15,[19][20][21][22][23] and major depressive disorder (9%-31%) during different periods of follow-up. [10][11][12][13][14] A systematic review, which included 51 prospective studies, that evaluated poststroke depression (PSD) (minor and major depressions), mainly based on the Diagnostic and Statistical Manual of Mental Disorders, Third and Fourth Editions, estimated that about 33% of all stroke survivors experienced depressive symptoms from 1 to 6 months after an acute event.…”
Section: Introductionmentioning
confidence: 99%